Japan-China 2008 Agreement: Common-Pool Resource Governance Problem - Rafyoga Jehan Pratama Irsadanar; Kan Kimura (Universitas Muhammadiyah Yogyakarta, 2021)
This research aims to answer the reason behind the stalled progress of dispute settlement in East China Sea between Japan and China, despite a high initial commitment to cooperate under